Censorship and the Law: Balancing Public Interest and Free Speech - Shuaib, Farid Sufian (2012)

(untitled)
A free media is a bedrock of democracy as espoused by the Prime Minister Dato' Sri Mohd Najib since without a free media reporting uncomfortable truths about the government how could the populace participate in governance. However, absolute freedom has no place in any country since absolute freedom will lead to anarchy. The task then is to strike a balance between a free media and competing individual and societal interests. The objective of this paper is to look at constitutional guarantee of free media and restrictions imposed upon the media and provide a legal analysis on the guarantee of free media, the restrictive laws and the application of the laws. The recent development on media laws where the government had loosen restrictive laws such as the scrapping off the annual newspaper licence is considered together with the need for further liberalisation of media laws to produce media that is vibrant, transparent and fair.